Translators’ Perspectives: The Construction of the Peruvian Indigenous Languages Act in Indigenous Languages - De Pedro Ricoy, Raquel; Howard, Rosaleen; Andrade Ciudad, Luis (Meta, 2018)
An urgent need is emerging in contemporary Latin America for the translation of legal texts from the languages of former European colonial powers into the many indigenous languages spoken across the region. This article addresses the issue in relation to the rise of legislation that requires States to uphold the principle of linguistic human rights. It takes as a case study the translation of the Peruvian Indigenous Languages Act (2011) from Spanish into five Amerindian languages, viewed as a postcolonial practice situated at the communicative interface between the State and the country’s indigenous populations. Our specific interest is the strategic behavior of the indigenous translators, as described by themselves, when communicating to their peoples the State norms contained in the Indigenous Languages Act. In order to analyze this behavior, we depart from text-analytical models and favor an approach based on the translators’ perceptions of their role and their rationales for the translation solutions adopted. The analysis combines theoretical strands from translation studies, legal studies and postcolonial studies so as to throw light on the translation of legal discourse from Spanish into the indigenous languages of Peru, as conducted, crucially, by bilingual translators situated on the cultural “inside.”